Associations between glycaemic deterioration and aortic stiffness and central blood pressure: the ADDITION-PRO Study. Issue 9 (September 2017) - Johansen, Nanna B.; Rasmussen, Signe S.; Wiinberg, Niels; Vistisen, Dorte; Jørgensen, Marit E.; Pedersen, Erling B.; Lauritzen, Torsten; Sandbæk, Annelli; Witte, Daniel R.
Abstract : Objectives: In the context of screening for diabetes, we examined levels of central haemodynamics among individuals with different levels of diabetes risk and analysed the impact of glycated haemoglobin A (HbA1c ) and HbA1c changes on central haemodynamics. Methods: A Danish population-based stepwise screening programme for diabetes including a diabetes risk score (DRS) questionnaire and glucose measurements identified seven groups of individuals at increasing levels of diabetes risk. After 7.8 years of follow-up, 2048 individuals underwent aortic stiffness assessment by carotid–femoral pulse wave velocity (aPWV) and assessment of central blood pressure (BP). We compared differences in central haemodynamics at follow-up between the diabetes risk groups and analysed the impact of HbA1c at screening and HbA1c change on central haemodynamics at follow-up adjusting for relevant confounders. Results: At screening, median age was 59.0 years, and median HbA1c was 5.7%. At follow-up, median aPWV was 8.0 m/s, and median central SBP was 123.5 mmHg. Among individuals with high DRS, aPWV, central SBP and DBP, and pulse pressure were higher in individuals with impaired glucose tolerance than normal glucose tolerance. Per 1%-point higher HbA1c at screening, aPWV was 0.23 m/s (95% confidence interval: 0.00; 0.46) higher, and central DBP was 1.35 mmHg (95% confidence interval: 0.19; 2.51) lower, whereas HbA1c change was not associated with any of the central haemodynamics. Conclusion: Dysglycaemia is associated with future aortic stiffness. However, glycaemic deterioration over 7.8 years does not affect aortic stiffness or central BP independently of other cardiometabolic risk factors. Abstract : Supplemental Digital Content is available in the text